(untitled) (International Journal of Environmental Sciences, 2025)
Aims: The aim is to study is to find the correlation between trunk- impairment scale (TIS) and PDMS-2 scale subcomponents stationary and locomotion. Methods: This observational study included a sample of 70 children diagnosed with cerebral palsy, aged between 60 and 64 months. Participants of both genders were assessed and enrolled in the study following the acquisition of informed consent from their parents. The Trunk Impairment Scale and PDMS-2 (Stationary and Locomotion subtests) were administered following standard manual guidelines for evaluation. Results: A descriptive analysis of the baseline characteristics was performed using the mean and standard deviation. To investigate the association between the PDMS-2 subtests stationary and locomotion raw scores and the Trunk Impairment Scale (TIS), Karl Pearson’s correlation coefficient was used. We assessed GMFCS level and TIS Scores which showed level I as (19.47#2.03) where level V as (2.14+2.73) between TIS and PDMS-2 (stationary and locomotion). It showed a positive correlation in Stationary (r=0.8155) and locomotion (r=0.8386). The study revealed a positive association between the Trunk Impairment Scale (TIS) scores and the PDMS-2 subtests for stationary and locomotion skills. Data were analyzed using SPSS (Statistical Package for the Social Sciences), version 21.0. Conclusion: The correlation between PDMS-2 and TIS in children with cerebral palsy demonstrated a positive relationship. Further the study can be explored in other Neurodevelopmental conditions at different ages various conditions and stages.